2022
DOI: 10.3389/fpsyt.2022.928145
|View full text |Cite
|
Sign up to set email alerts
|

P300 Modulation via Transcranial Alternating Current Stimulation in Adult Attention-Deficit/Hyperactivity Disorder: A Crossover Study

Abstract: ObjectiveA repeated finding regarding event-related potentials (ERPs) is that patients with ADHD show a reduced P300 amplitude. This raises the question of whether the attention of ADHD patients can be increased by stabilizing the P300. Assuming that the P300 is generated by event-related oscillations (EROs) in the low frequency range (0–8 Hz), one approach to increase the P300 could be to stimulate the patient’s P300 underlying ERO by means of transcranial alternating current stimulation (tACS). The aim of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 130 publications
0
8
0
1
Order By: Relevance
“…One study [ 46 ] applied a single session of 1 to 8 Hz over C1/C2 and C5/C6, without any cognitive improvement. This study also evaluated the P300 over centro-parietal regions, based on the hypothesis of reduced P300 generated by low frequency event-related oscillations (EROs), without any significant change.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…One study [ 46 ] applied a single session of 1 to 8 Hz over C1/C2 and C5/C6, without any cognitive improvement. This study also evaluated the P300 over centro-parietal regions, based on the hypothesis of reduced P300 generated by low frequency event-related oscillations (EROs), without any significant change.…”
Section: Resultsmentioning
confidence: 99%
“…Randomized control trials (RCT) were assessed according to the Cochrane database RoB 2 tool [ 52 ], with the assessed domains being randomization process, deviations from intended interventions, missing outcome data, measurement of the outcome, selection of the reported result and overall bias. Out of 15 RCT, three were evaluated as “Some concerns” due to single-blind design [ 23 , 46 , 47 ], two due to insufficiently described statistical analysis [ 21 , 35 ], one due to unsuccessful blinding integrity [ 41 ], and one due to insufficiently described blinding procedure [ 48 ]. Eight studies were considered “Low risk” [ 22 , 28 , 29 , 34 , 40 , 42 , 49 , 50 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, to our knowledge, only three studies have so far explored tACS as treatment for adult ADHD (Dallmer-Zerbe et al, 2020;Farokhzadi et al, 2020;Kannen et al, 2022). While one of the studies compared tACS to methylphenidate (Farokhzadi et al, 2020) and reported tACS as an effective treatment, the other two studies investigated tACS as an alternative treatment for ADHD by trying to increase the P300 amplitude (Dallmer-Zerbe et al, 2020;Kannen et al, 2022), which is considered to be diminished in ADHD patients (Hasler et al, 2016;Marquardt et al, 2018;Kaiser et al, 2020). Dallmer-Zerbe et al (2020) observed an increase in the P300 amplitude accompanied by a decrease in omission errors among adult ADHD patients, whereas Kannen et al (2022) did not confirm these results.…”
Section: Introductionmentioning
confidence: 99%